Exploration of the Reform of the Teaching Model of History Theory in Art Majors under the Perspective of Expectation - Wang, Linlin (Journal of Theory and Practice of Contemporary Education, 2023)
The "National Conference on Undergraduate Education in Higher Education Institutions in the New Era" emphasizes the need to "accelerate the construction of high-level undergraduate education and comprehensively improve talent cultivation capabilities". In current higher education, students' subjective initiative has become more prominent, especially for art students. Their weak foundation in literature and history, as well as a greater emphasis on technology in employment, have led them to prefer practical courses, and their indifference to historical theory courses has become a common phenomenon. This requires major universities to build high-level undergraduate education, It is necessary to reform and innovate the teaching mode of historical theory courses in art majors with students as the main body. In the perspective of "expectation", more attention is paid to the aesthetic expectations of the audience, and as a guide, attention is paid to students' "expectations". Only in this way can historical theory courses take on a new look, and art students' acceptance and initiative of historical theory be improved to the best state, achieving an effective combination of theory and practice.